Social media and digital marketing perceptions: Intra- and Inter-generational similarities and differences among Gen X, Y and Z - Anoop Gurunathan, A, K S Lakshmi (Journal of Informatics Education and Research, 2025)
This study explores the intra- and inter-generational similarities and differences in the perceptions of generations X, Y, and Z towards social media and digital marketing. Previous research articles in Google Scholar and Research Gate databases were referred for this purpose. Traditional media has more influence on GenX than online media. Differences do occur within generations hence, homogeneity of generations is questionable. Single online platform marketing may not be effective in influencing all generations as their preferences differ and therefore a multi-online platform approach with an omni-channel presence is warranted. Intra- and inter-generational differences and similarities in perceptions need to be looked upon while promoting the products and services. Though extensive studies have been conducted on the perceptions of generations towards social media and digital marketing, there is a gap and a need to explore further the intra- and inter-generational differences and similarities among GenX, Y, and Z.